2020
DOI: 10.1021/acs.iecr.0c01194
|View full text |Cite
|
Sign up to set email alerts
|

Easy and Rapid Synthesis of Carbon Quantum Dots from Mortiño (Vaccinium Meridionale Swartz) Extract for Use as Green Tracers in the Oil and Gas Industry: Lab-to-Field Trial Development in Colombia

Abstract: The main objective of this study is to develop nanotechnology-based materials, specifically carbon quantum dots (CQDs), as alternative nonpolluting, nontoxic, and easily manipulated tracers for the oil industry using an easy and rapid synthesis from Mortinõ (Vaccinium meridionale Swartz) extract, a process that was evaluated in the laboratory and subjected to a Colombian oil field trial. The CQDs were synthesized using an easy and rapid microwave-assisted carbonization (MWC) methodology involving aqueous natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…The CsPbBr 3 /m-SiO 2 composite was also tested under very harsh conditions, including high temperature and salinity, which characterize the underground conditions that tracers, used in oil extraction wells, have to withstand. , Such tracers are employed in order to probe the efficiency of injection wells drilled for oil extraction. To do so, tracers are inserted in the injection well, and their presence is probed at the extraction well: an amount of recovered tracer at the extraction well and the speed at which the tracer travels through the well can give precious information about the efficiency of the injection well .…”
mentioning
confidence: 99%
“…The CsPbBr 3 /m-SiO 2 composite was also tested under very harsh conditions, including high temperature and salinity, which characterize the underground conditions that tracers, used in oil extraction wells, have to withstand. , Such tracers are employed in order to probe the efficiency of injection wells drilled for oil extraction. To do so, tracers are inserted in the injection well, and their presence is probed at the extraction well: an amount of recovered tracer at the extraction well and the speed at which the tracer travels through the well can give precious information about the efficiency of the injection well .…”
mentioning
confidence: 99%
“…Concentration of the CQDs at the producer wells, as a function of time during a waterflooding operation in a Colombian field. [Reproduced from Franco et al Copyright 2020, American Chemical Society, Washington, DC. ]…”
Section: Applications For Secondary Recovery and Enhanced Oil Recover...mentioning
confidence: 99%
“…Currently, many challenges arise from the use of interwell tracers in the oil and gas industry, including economic cost, environmental issues, and the difficulty of detection and quantification that requires robust equipment. However, recent studies [34][35][36]91 have shown that carbon-based fluorescent 0D nanomaterials are a reliable option for substituting conventional radioactive or FBA-like tracers. For example, Kanj et al 34 and Alaskar and Kosynkin 35 have employed "inexpensive and environmentally friendly nanoparticles" called A-Dots (Arab-D Dots) as tracers under real reservoir conditions.…”
Section: Applications For Secondary Recovery Andmentioning
confidence: 99%
See 2 more Smart Citations